2008
DOI: 10.1016/j.jpba.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The development of multiple probe microdialysis sampling in the stomach

Abstract: A multiple probe approach of implanting microdialysis probes into each separate tissue layer would better represent sampling from the stomach. Presently, microdialysis sampling experiments are performed with only a single probe in the submucosa to represent sampling from the stomach tissue. The focus of this research was to develop a four-probe microdialysis sampling design to simultaneously monitor the stomach lumen, mucosa, submucosa and in the blood of the rat. Due to the small outer diameter of the microdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Alternatives to solving an adsorption problem are to test different tubing materials that may act differently and/or to add 0.25 or 0.5% albumin to the perfusate. Woo and Lunte concluded that the microdialysis behavior of some compounds improved after adding albumin, but not all, and that lipophilicity per se was not the issue, making the problem difficult to solve (57). If the measures of adding albumin or changing tubing material do not solve the problem, it is recommended not to perform microdialysis.…”
Section: In Vitro Preparations and Adsorption To Tubings And Probementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives to solving an adsorption problem are to test different tubing materials that may act differently and/or to add 0.25 or 0.5% albumin to the perfusate. Woo and Lunte concluded that the microdialysis behavior of some compounds improved after adding albumin, but not all, and that lipophilicity per se was not the issue, making the problem difficult to solve (57). If the measures of adding albumin or changing tubing material do not solve the problem, it is recommended not to perform microdialysis.…”
Section: In Vitro Preparations and Adsorption To Tubings And Probementioning
confidence: 99%
“…If the measures of adding albumin or changing tubing material do not solve the problem, it is recommended not to perform microdialysis. More detailed recommendation on how to address the problem with adsorption can be found in the AAPS-FDA workshop white paper (16), as well as in (18,24,57,58). However, in the paper by Nirogi et al, a 60-min pre-equilibration was used, which may hide possible adsorption (58).…”
Section: In Vitro Preparations and Adsorption To Tubings And Probementioning
confidence: 99%
“…Saline was perfused through the microdialysis probe at a rate of 1 ml/min and fractions of dialysate were collected during 5-minute intervals. The microdialysis probe was equilibrated for 25 minutes and fractions were collected to determine the basal concentrations of cGMP concentrations in the submucosa (Woo and Lunte, 2008). Vehicle (D-glucose: 10 mg in H 2 O) was injected into the lumen of the colon loop and the collection of dialysate fractions was continued for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…(A) Following a 20-minute equilibration period, a sub-EC 50 concentration of linaclotide (6 nM) was added to the apical chamber for 20 minutes, followed by addition of a concentration of linaclotide inducing a maximum increase in I sc (1000 nM) for another 20-minute period. In a parallel experiment, colonic mucosa was pretreated with MK571 (20 mM) for 20 minutes prior to addition of linaclotide (6 and ( Woo and Lunte, 2008). Here, we measured for the first time in vivo linaclotide-induced cGMP efflux into the colonic submucosal layer.…”
Section: Mrp4 Modulates Gc-c-dependent Electrolyte and Cgmp Secretionmentioning
confidence: 99%
“…Most recent published works [39] involved a RP separation using UV detection at 300, 280 and 275 nm to monitor the absorption of salicylic acid (SA), caffeine and metoprolol in the stomach following …”
Section: Detectors Coupled With Hplc Analysismentioning
confidence: 99%